Analyzing swelling characteristic of Nata de Coco: A Study on quality control challenges and solutions - Yahya, Mirza Auly; Khairi, Amalya Nurul; Uddin, ABM Helal; Metaragakusuma, Andi Patiware (Journal of Halal Science and Research, 2025)
Nata de coco is a food product derived from fermented coconut water with the help of the bacterium Acetobacter xylinum. CV ABC is the company that always produces nata de coco and notices the quality of the product. The problem in this study lies in the product standard testing, which often results in deviations from the swelling capacity test and the oversized test, which do not comply with company standards, thereby reducing the quality of Nata de Coco products. This research activity aims to analyze and formulate solutions related to the factors that cause deviations in production results. The method used is quantitative, with a graphical control chart to determine the magnitude of deviations that occur in the swelling capacity test and oversize test. Fishbone diagrams are used to determine the factors causing nata de coco to deviations from company standards. The data is in the form of documentation of the results of the swelling capacity test and the oversized test of 15 data. Data collection used a random sampling technique, which involved taking 400-gram samples of nata de coco from each batch. The results of the 15-day analysis showed that the swelling capacity test did not meet company standards by 7 days, or 47%, and the oversized test did not meet the maximum limit by 4 days, or 27%. Factors that dominate the causes of irregularities are equipment and people. There is a need for machine standardization and employee discipline to maintain the quality of nata de coco.   Keywords: Nata de coco, Oversize, Swelling capacity.